Influence of Type 1 Diabetes Mellitus on the Ocular Biometry of Chinese Children - Ying Xiao; Tao Li; Yan Jia; Shanshan Wang; Chenhao Yang; Haidong Zou (Journal of Ophthalmology)
Purpose. To compare ocular biometry between children with type 1 diabetes mellitus (T1DM) and healthy children in China and to determine the correlation of ocular biometry with the glycosylated hemoglobin (HbA1c) level and diabetes duration. Methods. A case-control study was conducted at Children’s Hospital of Fudan University between T1DM children and healthy children. The participants were evaluated for central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), K1 and K2 keratometry, and axial length (AL); also cycloplegic refraction was performed, and spherical equivalent (SE) was acquired. HbA1c levels of the T1DM cases were obtained. Results. Fifty-four eyes of 54 children with T1DM and 53 eyes of 53 healthy children were included. The mean age of T1DM group and control group was 10.59 ± 3.40 years and 9.55 ± 1.89 years, respectively, and the differences between age and gender were not significant (p=0.052, p=0.700). The mean LT in T1DM group (3.49 ± 0.18 mm) was thicker than that in the control group (3.40 ± 0.16 mm) (p=0.018), the mean ACD in T1DM group (3.52 ± 0.26 mm) was shallower than that in the control group (3.72 ± 0.26 mm) (p<0.001), and there were no significant differences of CCT, K1, K2, AL, and SE (p=0.088, p=0.672, p=0.821, p=0.094, and p=0.306, respectively). There was no significant correlation between HbA1c or diabetes duration and ocular biometry. Conclusions. Thicker LT and shallower ACD occurred in T1DM children rather than age-matched and sex-matched healthy children, but the overall refraction was not affected. HbA1c or diabetes duration was not correlated with ocular biometry in T1DM children.